RANCANG BANGUN SISTEM INFORMASI AKUNTANSI PENJUALAN DENGAN MODEL WATERFALL BERBASIS JAVA DESKTOP - Nurul Muthia; Hilda Amalia; Ari Puspita; Ade Fitria Lestari (LPPM Nusa Mandiri, 2019)
Every business entity is required to be able to improve their services to customers. With good service it will increase customer satisfaction so that it ultimately increases profits from the business entity itself. To be able to improve service to customers, business entities must be able to present an efficient and accurate sales transaction process. For this reason, sales information system design is needed. Sales accounting information system can streamline the sales transaction process and can produce sales reports that are more accurate and timely and able to record accounting transactions in a short time. Timely and accurate sales reports are needed for the decision making process for business entity owners. The research objective is to develop software using the waterfall device development method, so that it can produce software that is able to improve sales system work and increase profits. The design results of the sales information system using the waterfall method can reduce errors caused by human factors (avoiding human error), avoiding the combination of data entry and presentation of sales reports presented in a fast and precise time so as to help the owner to make the decision making process .